A Systematic Review of Linear Programming Techniques as Applied to Diet Optimisation and Opportunities for Improvement - Donkor, L.; Essien, E.; Afrifah, N.S. (Journal of Optimization, 2023)
Food provides the required nutrients for adequate growth and development. However, meeting the recommended nutrients while considering environmental sustainability can be complicated and challenging. Previously, trial-and-error methods were used for product development, but these are tedious and time-consuming. Mathematical techniques such as linear programming offer an alternative and rapid approach to developing products with nutritional and/or sustainability considerations. Tis method has been extensively used in diet optimisation but does not satisfactorily address dietary problems with more than one objective function. Aim. The review aimed to explore the extent of mathematical approaches to addressing dietary problems. Methodology. A systematic review approach was adopted for the research. The major search engines used were Scopus, PubMed, and and Science Direct, based on selected keywords. A stepwise structural method was used to obtain articles. Articles that contained The search keywords that were applied in nonhuman cases were excluded. Duplicated articles were also excluded and accounted for as one. All articles were subjected to further review based on their abstract and complete titles before passing them for data analysis. Results. The total number of articles obtained from the search activity was 280. Fifty-six were retained after the criteria for inclusion were applied to them. Out of the 56 articles retained, only two studies used goal programming and nonlinear generalised mathematical approaches to address dietary problems. All other studies used the linear programming approach, focusing mainly on one or two constraints (nutrients and/or acceptability), highlighting the limitations of linear programming in addressing the multiple factors of a sustainable diet. Several researchers have proposed using multiobjective optimisation, an extension of linear programming to address challenges with sustainable diets. These approaches can be further explored to address sustainable dietary problems.
Research Article
Keywords: Linear Programming Techniques; nutrition; Diet